A practical blockchain-based framework for anti-counterfeiting and traceability - Hung Ho Dac; Len Van Vo; The Bao Nguyen; Cao Hoai Phuong Nguyen; Van Huu Tran (CTU Journal of Innovation and Sustainable Development)
Blockchain has features that help systems overcome the inherent limitations of traditional centralized approaches. Integrating blockchain technologies into systems to improve security, privacy, and transparency is a prominent trend. Currently, consumers are very concerned about the origin and the legitimacy of the products, so it is necessary to strengthen anti-counterfeiting and traceability in product management. Many theoretical approaches have been proposed recently. In this study, we propose a practical framework based on blockchain that supports anti-counterfeiting and traceability. Based on the proposed practical framework, we implemented a pattern as a proof-of-concept of the approach. We conduct experiments at Thu Dau Mot University, a pioneer in the production and transfer of biotechnology. The results show feasibility and good results regarding the proposed practical framework. Moreover, we also published our code base to GitHub with an open license.